Pengaruh Sistem Pengendalian Internal dan Kompetensi Terhadap Fraud - Febri Putri Astuti; Aris Eddy Sarwono (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect of the internal control system and competence on fraud. The research population is the employees of the Hospital. The type of data used is Primary data. The research sample was selected through purposive sampling. Internal control systems and competencies according to research have a significant impact on fraud.